HUBUNGAN ANTARA INTENSITAS BERMAIN GAME ONLINE DENGAN KUALITAS TIDUR PADA REMAJA - Ayu Deka Wati; Yuniza Yuniza (Masker Medika, 2023)
Background: Adolescence is a period of transition or transition from children to adulthood. At this time so rapidly experiencing growth and development both physically and mentally. The basic need of every living thing for its survival is sleep. Sleep is part of the body's biological rhythm to restore stamina. Sleep needs in general range from 6-8 hours per day. Another impact of online games is the reduced rest time where online game users play without knowing the time this greatly affects the quality of sleep. Purpose : To determine the relationship between the intensity of playing online games with sleep quality in adolescents at SMP Negeri 35 Palembang. Methods: non-experimental quantitative research with a cross sectional approach, the sampling method used purposive sampling technique with a sample of 66 respondents using the chi square statistical test. Results: From a total of 66 respondents of Junior High School 35 Palembang that the number of respondents with the intensity of playing games in the category is sometimes (92.4%) and the intensity of playing games is always (7.6%). From a total of 66 adolescent respondents at SMP N 35 Palembang, the number of respondents with good sleep quality (92.4%) and poor sleep quality (7.6%). There is a significant relationship between the intensity of playing games with sleep quality in adolescents at SMP N 35. Palembang in 2022. The results of statistical tests using the Chi square test value P value = 0.00 or 0.05. Conclusion: there is a relationship between the frequency of playing games in adolescents with the intensity of sleep. Keywords: Sleep quality, Online games, Teenagers